Arts council lands grants for $25,000 (Raton, NM Raton Range, 1991)
The article is about the New Mexico Art Division awarding more than $33,000 to organizations in Colfax County. Gives details of how much was awarded and to which organization.
2 paged newspaper article
Master list item #: 12
File location is in the Raton file Cabinet
Keywords: New Mexico Arts Division; Arts and Humanitie Council; Hispanic Arts Committee; Touring Incentive; New Mexico Grants; Colfax County